P004 ASSESSMENT OF A BRAZIL'S REFERENCE CENTER USING "QUALITY OF CARE THROUGH THE EYES OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE" (QUOTE-IBD). (7th February 2019) - Takamune, Debora M; Cury, Giovana S; de Barros, Jaqueline R; Baima, Julio P; Saad-Hossne, Rogerio; Sassaki, Ligia Y
Abstract: Background: The Inflammatory Bowel Diseases (IBD) are recurrent and chronic, demanding frequent interaction between patient and healthcare services. Quality of care (QC) is a factor that interferes in treatment and quality of life improvement. It is required to evaluate QC conditions and improve its shortcomings. Methods: This cross-sectional study included 38 patients with confirmed IBD diagnosis (either Crohn's Disease – CD – or Ulcerative Colitis – UC) from a single IBD Center (Hospital das Clínicas de Botucatu) of São Paulo State, Brazil. Disease activity was evaluated through Crohn's Disease Activity Index (CDAI) and Mayo Score, in CD and UC patients, respectively. QC was evaluated through QUOTE-IBD (questionnaire to assess quality of care through the patient's eyes), which is composed by 10 generic and 13 IBD specific items and measures 8 dimensions of care: accessibility, costs, accommodation, continuity of care, courtesy, information, competence, autonomy. Each category is graded from 0 to 10, being considered satisfactory if graded 9 or above. Statistical analysis: descriptive. Results: 21 CD patients and 17 UC patients were interviewed. The average age was 31.11 ± 9.32 years and 63.16% were women. The mean duration of the disease was 6.35 ± 4.98 years and most patients were in remission in both the UC (64.71%) and the CD (76.19%) groups. Regarding the disease impact on the patient's life, 81.82% of them declared having missed school or work, 18.18% had trouble with that and 39.47% referred that IBD limits routine activities. Despite that, 94.74% of patients feel confident about the treatment. According to the healthcare evaluation, the total QUOTE punctuation was 8.65 ± 1.39, classifying the QC as unsatisfactory. The following QUOTE categories were classified as satisfactory: courtesy (9.24 ± 1.28) and costs (9.34 ± 2.11); the following were considered unsatisfactory: accessibility (7.99/1.87), accommodation (8.24/2.81), continuity of care (8.17/2.68), information (8.85/2.12), competence (8.46/1.92) and autonomy (8.89/2.97). Conclusions: The acquired data show that, even though there is a near-satisfactory QC, there are many issues that must be improved, especially the healthcare structure and the doctor-patient relationship, both pillars of a successful treatment. Service quality assessment is necessary for us to identify health care areas that might need improvement, both at the level of individual care (e.g., information about nutrition, autonomy) and in the dimensions of care (e.g., accessibility and competence). Thus, the final aim of this study, to offer a better treatment for IBD patients, will be possible.